Non‐alcoholic fatty liver disease and the development of reflux esophagitis: A cohort study. Issue 5 (15th February 2018) - Min, Yang Won; Kim, Youngha; Gwak, Geum‐Youn; Gu, Seonhye; Kang, Danbee; Cho, Soo Jin; Guallar, Eliseo; Cho, Juhee; Sinn, Dong Hyun
Abstract: Background and Aim: Non‐alcoholic fatty liver disease (NAFLD), a hepatic manifestation of the metabolic syndrome, is associated with gastroesophageal reflux disease in cross‐sectional studies, but a prospective association has not been evaluated. The current study aimed to determine whether NAFLD increases the risk of incident reflux esophagitis in a large cohort study. Methods: We conducted a cohort study of 34 063 men and women without reflux esophagitis or other upper gastrointestinal disease at baseline who underwent health checkup examinations between January 2003 and December 2013. Fatty liver was diagnosed by ultrasound based on standard criteria. Reflux esophagitis was defined by the presence of at least grade A mucosal break on esophagogastroduodenoscopy. Results: The prevalence of NAFLD at baseline was 33.2%. During 153 520.2 person‐years of follow‐up, the cumulative incidences of reflux esophagitis for participants without and with NAFLD were 9.6% and 13.8%, respectively ( P < 0.001). The age‐adjusted and sex‐adjusted hazard ratio for the risk of reflux esophagitis development in participants with NAFLD compared with those without NAFLD was 1.15 (95% confidence interval 1.07–1.23; P < 0.001). However, this association disappeared after adjusting for body mass index and other metabolic factors (hazard ratio 1.01, 95% confidence interval 0.94–1.09; P = 0.79). Similarly, in multivariable‐adjusted models, there was no significant association between NAFLD severity and the risk of developing reflux esophagitis. Conclusions: Non‐alcoholic fatty liver disease is not independently associated with the risk of the development of reflux esophagitis, but rather, reflux esophagitis is primarily the consequence of increased body mass index commonly associated with NAFLD.